Case Study of Asmaul Husna Listening Therapy to Lower the Scale of Pain in Head Injury Patient - Hidayat, Nur; Noor Sofia, Maulidah; Nugraha, Yuda; Oktriani, Herni; Setiawan, Henri (Yayasan Inspirasi El Burhani, 2022)
Objective: This case study was conducted to describe the intervention of Asmaul Husna in reducing pain in patients with head injuries. Method: This study uses a case study design with an evidence-based practice implementation approach that focuses on nursing interventions. The study was conducted at the BLUD RSU Banjar City on 25-27 May 2022. The participant in this study was a patient 35 years old, male, who complains of pain in the back of the head. The process of assessing and establishing a diagnosis is focused on the main problem. Objective and subjective data become a reference for periodic evaluation of nursing implementation. And the researchers measured the pain scale using the Numerical Rating Scale (NRS) measurement design. Result: The patient acknowledged that the pain decreased after the Asmaul Husna intervention was given. Asmaul Husna's intervention should be suspected of being effective in reducing pain in patients with mild head injuries as evidenced by subjective patient recognition, although it has not been supported by a normal pulse rate as an indicator of physical health. Conclusion: Theoretically, this research does not conflict with previous research so it can be a reference in future research. Clinically, Asmaul Husna intervention can be an alternative intervention to reduce pain scale in patients with chronic diseases such as head injuries in hospitals and health centers.